The Influence of Personality, Attachment, and Fatigue on Employee Turnover Intention of PT. ACTIVEWEAR - Fadhilah Baitu Tauhid, Lintang Buana; Kartono, Kartono (Jurnal Ekuisci, 2026)
Background. The high turnover rate in the manufacturing industry demonstrates the need for a comprehensive understanding of the psychological factors and working conditions that influence employees' decisions to stay or leave the organization. Purpose. This study aims to analyze the influence of personality, work attachment, and work fatigue on employees' turnover intention at PT. Seyang Activewear Cirebon. Method. This study uses a quantitative approach with a causal associative design. Data were collected using a Likert-scale questionnaire from 285 respondents selected through accidental sampling. Data analysis was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4.0. Results. The results showed that personality and work attachment had a negative, significant effect on turnover intention, while work fatigue had a positive, significant effect. Simultaneously, these three variables explained 55.2% of the variation in employee turnover intention. Conclusion. Work fatigue is the dominant factor in increasing job change intention, while adaptive personality and work attachment play a protective role. These findings confirm that turnover intention is influenced by the interaction between individual characteristics and work-related psychological conditions. Implementation. This study recommends that companies integrate personality management, strengthen work attachment, and manage work fatigue into their human resource management strategies to improve employee retention sustainably.